Merkmale guter inklusiver Schulen – Zusammenhänge auf Lehrkraft-Ebene - Wohnhas, Verena; Böhm-Kasper, Oliver; Neumann, Phillip (PraxisForschungLehrer*innenBildung. Zeitschrift für Schul- und Professionsentwicklung)
Der Beitrag beschäftigt sich mit der Frage, ob die Merkmale guter inklusiver Schulen – verstanden als Schulentwicklungsinstrument – mit der Arbeitszufriedenheit und den Selbstwirksamkeitsüberzeugungen von Lehrkräften in inklusiven Gesamt- und Sekundarschulen zusammenhängen. Dazu werden Daten aus dem BMBF-geförderten Projekt BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) von N = 119 Lehrkräften analysiert. Die Ergebnisse zeigen, dass die Merkmale guter inklusiver Schulen einen großen Teil der Varianz in der Arbeitszufriedenheit aufklären. Die kollektive Selbstwirksamkeitsüberzeugung korreliert stark mit den Merk-malen guter inklusiver Schulen und der Arbeitszufriedenheit der Lehrkräfte. Für die individuelle inklusionsbezogene Selbstwirksamkeitsüberzeugung zeigen sich itemspezifische Befunde, die diskutiert werden. Implikationen für die schulische Praxis werden abgeleitet.
Keywords: Arbeitszufriedenheit; Inklusion; Merkmale guter inklusiver Schulen; Selbstwirksamkeit; kollektive Selbstwirksamkeitsüberzeugung

Model‐Based Optimization Framework for Catalyst Dilution Applications in CO2‐Methanation Reactors - Schmücker, Torben; Riese, Julia (Chemie Ingenieur Technik)
ABSTRACT Methane, synthesized from renewable hydrogen and biogenic CO 2 , can be a part of the transformation towards renewable energy carriers. A major engineering challenge is the optimization of the fixed‐bed reactor design, specifically the heat dissipation in regions of high reaction heat release. A mitigation concept is the introduction of inert material into the fixed bed, called catalyst dilution. In this study, a 1D continuity model is presented, which aims to predict catalyst superheating. This model is used in an exploratory study to identify system sensitivity and optimization parameters. Subsequently, an optimization framework for improving the reactor design is tested, resulting in a 148‐K reduction in peak catalyst temperature when using a 33.3 vol% catalyst dilution.

Parental (dis)satisfaction with school placement to achieve inclusion: a cross-country comparison - Johansson, Veslemøy Maria Fossum; Gibson, Suanne; Woodcock, Stuart; Dechsling, Anders; Kullmann, Harry; Herrebrøden, Marte Karoline; Ulriksen, Line Britt; Nordahl-Hansen, Anders (Frontiers in Education)
Background – This study draws on data from a larger international project exploring parents' perceptions of the education of their children with special educational needs and/or disabilities (SEND). Using responses from 1, 309 parents in Australia, England, Germany, and Norway it examines parental satisfaction with mainstream and special schools, and parents' school placement preferences, including willingness to change schools. Parental satisfaction is assessed as an overall evaluation of how well the child's school placement meets their needs, without distinguishing between specific aspects of the school experience. The study also explores whether the child's level of support is associated with these perceptions. Based on a human rights perspective, we highlight parents’ perspectives and their role in the development of more inclusive education systems, without promoting one model of schooling over another. Methods – Responses from 1, 309 parents across four countries were analysed using descriptive and inferential statistics. Non-parametric tests compared satisfaction across school types, chi-squared tests assessed associations with willingness to change schools, and binary logistic regression examined whether level of support was associated with parents' willingness to change school placement. Results – Parents in England, Germany, and Norway reported higher satisfaction with special schools than with mainstream schools. No statistically significant difference was observed in Australia. Parents of children in special schools were less likely to report considering changing schools, particularly in England and Norway. Higher pupil support needs were significantly associated with parents’ willingness to change school across the combined sample. These findings suggest that parental satisfaction with their child's education and their preferences regarding school placement may be shaped by both school type and how well pupils' support needs are perceived to be met. Discussion and conclusion – The role of parents as key stakeholders in developing inclusive education systems, consistent with the Convention on the Rights of Persons with Disabilities (CRPD) is emphasised. While parents in special schools in three of the four countries reported higher satisfaction, the reasons for this remain unclear. Understanding the factors shaping parental satisfaction is essential for developing inclusive and responsive learning environments. These findings offer a starting point for future research on how education systems can better align policy commitments with families’ lived experiences.
Keywords: human rights; inclusion; inclusive education; international study; parents; school development; special educational needs

Microfoundations of Absorptive Capacity as Revealed by Inventor Deaths - Balsmeier, Benjamin; Fleming, Lee; Lück, Sonja (Management Science)
We return to the theoretical foundations of absorptive capacity and test the idea that personal experience in a field makes it easier for a firm’s inventors to recognize and build upon knowledge in that field from other local firms. We propose a new empirical model of localized knowledge diffusion, which (1) measures a firm’s absorptive capacity by its inventors’ prior experience in a field, (2) uses a death instrument to exogenously vary the availability of knowledge of the same collaborative patent in different regions, and (3) estimates the difference in citation likelihood from all subsequent inventors across both regions as a function of a potentially citing inventor’s prior experience in the field. Consistent with the original theory of absorptive capacity, firms whose inventors have prior experience in a field are more likely to use locally available interpersonal knowledge from other firms; furthermore, this effect declines monotonically with distance. Although the effects strengthen for more recent experience and multidisciplinary knowledge, the greatest benefits accrue to firms in the interaction—those whose inventors have more recent experience and that seek to absorb multidisciplinary knowledge. Interpersonal absorptive capacity within firms does not appear to localize. This paper was accepted by Anita McGahan, business strategy. Funding: The authors acknowledge financial support from the Alfred P. Sloan Foundation and the National Science Foundation [Grant 1360228]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2024.06147 .

Praxisforschung in Schule und Unterricht

Three pitfalls in intercultural education: Cultural uniformity, pedagogical neutrality, and presumptions of competence - Pöllmann, Andreas (Globalisation, Societies and Education)
This article critically examines three persistent pitfalls that undermine the transformative potential of intercultural education: cultural uniformity, pedagogical neutrality, and presumptions of competence. These interconnected tendencies are rooted in essentialist conceptions of culture, the depoliticisation of educational practice, and the instrumental reduction of intercultural competence to a measurable skill. Drawing on critical pedagogy and decolonial scholarship, as well as empirical studies on monolingualism, assimilationism, and institutionalised hierarchies, the article demonstrates how well-intentioned initiatives often reproduce structural power asymmetries, symbolic violence, and epistemic marginalisation. It thus advocates an intercultural education grounded in critical reflexivity, political responsibility, and a sustained commitment to epistemic and social justice. Moving beyond reductive frameworks, the article advances dialogic, participatory, and decolonising approaches that interrogate dominant norms, recognise the pluriform and situated character of knowledge, and foreground the relational dynamics of interculturality. Intercultural learning is thus reframed as an ongoing, power-conscious process of negotiating difference within structurally unequal conditions rather than as the transmission of predefined competencies.

Adapting the HVOF Process for the Repair of Twin-Roll-Caster Shells - Lauth, Martin; Hoyer, Kay-Peter; Voswinkel, Dietrich; Gräfen, Winfried; Schaper, Mirko (HTM Journal of Heat Treatment and Materials)
Abstract Roller shells of twin-roll-caster (TRC) are subjected to wear and tear due to their usage in harsh casting and forming conditions. Therefore, their durability is significantly shortened by the need to refinish the surface to reinstate suitable surface parameters for rolling and casting thin aluminium or other metal strips. To extend the lifetime of the rollers, a solution to repair the surface has to be found. Due to the constraints in the TRC process, most surface repair processes are not suitable, too complex (multistage heat treatment) or too expensive. Hence, high velocity oxygen fuel (HVOF) is a viable solution for applying a repair surface onto worn-down rollers, as this process is well-known and understood, already established in the industry, and potentially possible to integrate into the TRC process environment without disassembling the roller from the machine.

Adapting the HVOF Process for the Repair of Twin-Roll-Caster Shells - Lauth, Martin; Hoyer, Kay-Peter; Voswinkel, Dietrich; Gräfen, Winfried; Schaper, Mirko (HTM Journal of Heat Treatment and Materials)
Abstract Roller shells of twin-roll-caster (TRC) are subjected to wear and tear due to their usage in harsh casting and forming conditions. Therefore, their durability is significantly shortened by the need to refinish the surface to reinstate suitable surface parameters for rolling and casting thin aluminium or other metal strips. To extend the lifetime of the rollers, a solution to repair the surface has to be found. Due to the constraints in the TRC process, most surface repair processes are not suitable, too complex (multistage heat treatment) or too expensive. Hence, high velocity oxygen fuel (HVOF) is a viable solution for applying a repair surface onto worn-down rollers, as this process is well-known and understood, already established in the industry, and potentially possible to integrate into the TRC process environment without disassembling the roller from the machine.

bwp@ Spezial HT2025: Nachhaltig – Digital – Chancengerecht. Zukunftsszenarien von Arbeit, Bildung und Beruf

Implementierung von Nachhaltigkeit in der Berufsvorbereitung – Konzeptionelle und praxisbezogene Entwicklungen - Hartwich, Katharina; Heisler, Dietmar (bwp@ Berufs- und Wirtschaftspädagogik – online)

Skills Help, but They Don’t Help All at Once: Changes in the Relationship Between Study- Relevant Skills and Student Stress as Well as Study Satisfaction During the First Two Years of Teacher Education - Sagolla, Nils; Seifert, Andreas; Bohndick, Carla; Buhl, Heike M. (Journal for Educational Research Online)

Verhaltensbezogene Prävention von Prokrastination: Das PROFI-Training - Kaemper, Mara; Buhl, Heike M.; Klingsieck, Katrin B. (Prokrastination: Erkennen, Verstehen, Reduzieren)

A product Meta Data Model of assembly-related extreme data to enable hybrid decision support - Gräßler, Iris; Vollenkemper, Felix; Pottebaum, Jens (1st International Symposium: March 24 – 26, 2026, Heinz Nixdorf Institute, Paderborn University)
Models of Circular Economy introduce circularity strategies like reuse, repair or remanufacture. A significant level of complexity is added when these strategies are applied not only on integrated product level, but on lower levels of assemblies and parts. Therefore, approaches, like Design for Assembly, Disassembly and Reassembly (DfADR) become increasingly important including the consideration of ADR capabilities. To put DfADR into practice, it is necessary to structure ADR-related product data and make it usable for product engineers. For instance, assemblies resulting from disassembly might not be consistent with original assembly structures. Therefore, a Product Meta Data Model (MDM) is required to handle assembly-related data even when it has extreme characteristics. A literature review on related MDMs reveals a range of models for general product data and identifies a gap in consideration of assembly-related data. In an expert workshop, requirements are raised to evaluate existing models and develop ADR-related extensions. The MDM is conceptually modelled and validated by competence questions. The paper presents an approach that makes assembly-related data usable for hybrid decision support and enables engineers to think ahead of ADR processes.

Trustworthy AI: Operationalizing Responsibility in Lifecycle-Aware AI Threat Modeling through RACI - Tahir, Faiza; Ullah, Ubaid; Bodden, Eric (Proceedings of the 21st International Conference on Software Technologies)

Static Analysis Traces can Help Dynamic Symbolic Execution: a Replication Study - Kummita, Sriteja; Schiebel, Fabian Benedikt; Bodden, Eric; Miao, Miao; Wei, Shiyi (2026 IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER))

Fibers, Textiles, and Dress - Droß-Krüpe, Kerstin; Grömer, K. (A Cultural History of Craft in Antiquity)

rota – ratio – res publica. Gesammelte Schriften Helmuth Schneider II

Private Peers’ Disclosure Transparency and Public Firms’ Information Environment - Beyer, Bianca; Flagmeier, Vanessa; Kosi, Urska
This study examines how private peers’ disclosure transparency affects public firms’ information environment, captured through analyst forecast behavior. Focusing on the most important private firms operating in U.S. industries, we investigate whether private peer disclosure—despite differing substantially from public firm disclosure—is incorporated into analysts’ forecasts. In a cross-sectional analysis, we document lower forecast quality in industries where private peers’ disclosure intensity is low. In contrast, when private peers’ disclosure intensity is high, forecast quality does not differ from that in industries with only public peers. We find consistent results for a subsample of U.S. private peers. Consistent with this interpretation, a difference-in-differences analysis documents increased analyst forecast activity around the disclosure dates of private peers. Together, these findings indicate that analysts incorporate private peers’ information when these peers are both economically important and sufficiently transparent, and highlight that variation in private firms’ disclosure intensity generates heterogenous externalities for public firms. Overall, our evidence supports a cost-benefit trade-off in analysts’ information acquisition, and, by documenting the relevance of private peers’ information for public firms, contributes to the debate on the externalities of private firms’ disclosure transparency.

INNOVADE Interdisciplinary Knowledge Base on Digital Democracy - D2.1 - Fuchs, Christian; Friesch, Kevin; Museba, Joel
This report outlines foundations of digital democracy and digital democracy research. It is structured into eight chapters: Chapter 1: Introduction Chapter 2: What is Digital Democracy? Chapter 3: Online Participation Chapter 4: Open Governance Chapter 5: Digital Activism Chapter 6: e-Voting Chapter 7: Global Trends that Influence Digital Democracy Chapter 8: Foreign Interferences in Democracy

Dissemination of information by small caps - Böing, Dennis; Kosi, Urska